2017
DOI: 10.1038/cddis.2017.237
|View full text |Cite
|
Sign up to set email alerts
|

HIV integrase inhibitor, Elvitegravir, impairs RAG functions and inhibits V(D)J recombination

Abstract: Integrase inhibitors are a class of antiretroviral drugs used for the treatment of AIDS that target HIV integrase, an enzyme responsible for integration of viral cDNA into host genome. RAG1, a critical enzyme involved in V(D)J recombination exhibits structural similarity to HIV integrase. We find that two integrase inhibitors, Raltegravir and Elvitegravir, interfered with the physiological functions of RAGs such as binding, cleavage and hairpin formation at the recombination signal sequence (RSS), though the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 61 publications
1
23
0
Order By: Relevance
“…A recent report has shown that Elvitegravir, an integrase inhibitor, can inhibit RAG functions both in vitro and in vivo, but not Raltegravir 20 . In the present study, we have investigated the impact of second-generation integrase inhibitor, Dolutegravir, on V(D)J recombinase and its action.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A recent report has shown that Elvitegravir, an integrase inhibitor, can inhibit RAG functions both in vitro and in vivo, but not Raltegravir 20 . In the present study, we have investigated the impact of second-generation integrase inhibitor, Dolutegravir, on V(D)J recombinase and its action.…”
Section: Resultsmentioning
confidence: 99%
“…Mice fed with Elvitegravir showed a decrease in maturation of B cells 20 . A significant abrogation of RAG1 activity in vitro and in vivo was observed for Elvitegravir, on the other hand Raltegravir caused limited abrogation of RAG1 activity in vitro 20 . There are also reports of high rate of Non-Hodgkin's lymphoma in patients undergoing treatment with integrase inhibitors as well as early onset of autoimmune diseases 21,22 .…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations